(untitled) (Politeja, 2016)
Political, economic and cultural connections between Afghanistan and South Asia have been long‑lasting and strong throughout the centuries, not only because of the geographical closeness of the regions, but also due to the genetic relationship of their peoples. In the 21st century, due to rapid geopolitical changes and globalization the mutual relations of these two regions are becoming more and more important, not only on bilateral level, but also from the point of view of the regional and international interests. The aim of this article is to concisely show how the relations between Afghanistan and South Asia developed over the history, with special attention given to the current state of affair.